Using SUpported Motivational InTerviewing (SUMIT) to increase physical activity for people with knee osteoarthritis: a pilot, feasibility randomised controlled trial - Bell, Emily Catherine; O'Halloran, Paul; Wallis, Jason A; Crossley, Kay M; Gibbs, Alison J; Lee, Annemarie; Jennings, Sophie; Barton, Christian J (BMJ open, 2023)
ObjectiveThe objective of this study was to determine the feasibility and effectiveness of using SUpported Motivational InTerviewing (SUMIT) to increase physical activity in people with knee osteoarthritis (KOA).DesignRandomised controlled trial.SettingWe recruited people who had completed Good Life with osteoArthritis Denmark (GLA:D) from private, public and community settings in Victoria, Australia.InterventionsParticipants were randomised to receive SUMIT or usual care. SUMIT comprised five motivational interviewing sessions targeting physical activity over 10 weeks, and access to a multimedia web-based platform.ParticipantsThirty-two participants were recruited (17 SUMIT, 15 control) including 22 females (69%).Outcome measuresFeasibility outcomes included recruitment rate, adherence to motivational interviewing, ActivPAL wear and drop-out rate. Effect sizes (ESs) were calculated for daily steps, stepping time, time with cadence >100 steps per minute, time in bouts >1 min; 6 min walk distance, Knee Osteoarthritis Outcome Score (KOOS) subscales (pain, symptoms, function, sport and recreation, and quality of life (QoL)), Euroqual, systolic blood pressure, body mass index, waist circumference, 30 s chair stand test and walking speed during 40 m walk test.ResultsAll feasibility criteria were achieved, with 32/63 eligible participants recruited over seven months; with all participants adhering to all motivational interviewing calls and achieving sufficient ActivPAL wear time, and only two drop-outs (6%).12/15 outcome measures showed at least a small effect (ES>0.2) favouring the SUMIT group, including daily time with cadence >100 steps per minute (ES=0.43). Two outcomes, walking speed (ES= 0.97) and KOOS QoL (ES=0.81), showed a large effect (ES>0.8).ConclusionSUMIT is feasible in people with knee osteoarthritis. Potential benefits included more time spent walking at moderate intensity, faster walking speeds and better QoL.Trial registration numberACTRN12621000267853.